2012
DOI: 10.1002/ibd.21861
|View full text |Cite
|
Sign up to set email alerts
|

Doctor Message Can Alter Patientsʼ Behavior and Attitudes Regarding Inflammatory Bowel Disease and Colon Cancer

Abstract: Patients who remember their doctor's messages are more likely to have a positive outlook about colonoscopies and IBD, have a better quality of life, undergo surveillance colonoscopies at the correct interval, and perceive cancer risk more realistically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…In our previous study, we measured doctor message about colonoscopy by formally validating our Doctor Told Scale in this same population of patients. 10 Although our Doctor Told Scale did correlate with chart-reported adherence (P , 0.01), it did not correlate with SE. Thus, although doctors may have spoken with patients about the colonoscopy procedure, we did not find that this communication was associated with improved SE.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In our previous study, we measured doctor message about colonoscopy by formally validating our Doctor Told Scale in this same population of patients. 10 Although our Doctor Told Scale did correlate with chart-reported adherence (P , 0.01), it did not correlate with SE. Thus, although doctors may have spoken with patients about the colonoscopy procedure, we did not find that this communication was associated with improved SE.…”
Section: Discussionmentioning
confidence: 61%
“…More detailed demographic data have been reported in our 2 previous studies with the same population of patients. 8,10 In all, 353 patients were included when creating the Colonoscopy SE scale, and 366 were included in the Top Five and Highly Certain SE Scales. Mean, range, and variance are included for all scale items in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…53 Some studies have shown that information recall is also particularly poor among those with limited health literacy. 44,54 Although research in IBD patients has demonstrated that recall of information from the clinical encounter is linked to perceptions of colonoscopy and colon cancer risk, 55 further studies are needed to examine the role of health literacy in cancer screening for patients with IBD. Notably, a 2014 study in Gastrointestinal Endoscopy found that the majority of professional societies' and popular Web sites' colorectal cancer online patient education materials were written well beyond the sixth grade reading level, and were lacking information aimed at patients' beliefs and perceptions of the risks, benefits, and barriers that could impact screening.…”
Section: Colon Cancer Screeningmentioning
confidence: 99%
“…69 Outlined below ( Table 1 and Table 2) are additional strategies that both providers and patients can use to bridge communication gaps and improve information recall, the latter of which has been linked to medication adherence 76 and quality of life in patients with IBD. 55 …”
Section: Case Examplementioning
confidence: 99%